2015
DOI: 10.2514/1.b35517
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Premixed Combustion with Varying Equivalence Ratio in Gas Turbine Combustor

Abstract: RANS simulation of a gas turbine combustor with complex geometry is performed. The turbulence is modelled using a two-equation approach. The scalar mixing and combustion is modelled using a flamelet based approach for partially premixed combustion. In this approach transport equations to described scalar mixing and reacting fields and their statistical interactions are solved along with standard conservation equations. The boundary conditions are specified using measured values. The computed spatial variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Thus, for an LES grid with a filter size similar to or larger than the typical laminar flame thickness, which is common in LES practice, the subgrid Z-c correlation can have a substantial effect on time-averaged statistics. This is consistent with the importance of Z-c correlation observed in previous RANS studies [7][8][9]12,13]. This is specifically so in flame stabilisation regions as can be seen in Figure 6 for x/D = 6.…”
Section: Significance Of Subgrid Covariancesupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, for an LES grid with a filter size similar to or larger than the typical laminar flame thickness, which is common in LES practice, the subgrid Z-c correlation can have a substantial effect on time-averaged statistics. This is consistent with the importance of Z-c correlation observed in previous RANS studies [7][8][9]12,13]. This is specifically so in flame stabilisation regions as can be seen in Figure 6 for x/D = 6.…”
Section: Significance Of Subgrid Covariancesupporting
confidence: 92%
“…Note that the two additional residual terms involving cross correlation between the temporal and spatial averaging procedures [10] are considered to be negligible for this study as in [11]. Previous RANS studies [7,8,12,13] showed that the total time-averaged correlation, {Z c }, is quite influential in partially premixed lifted flames. This was further confirmed in a recent experimental study by Barlow et al [5] showing a strong Z-c correlation in a partially premixed piloted jet flame.…”
Section: Introductionmentioning
confidence: 99%
“…(12) 11 keep the approach general and so it is followed here. This modelling approach worked well for various flames in a range of flow and combustion conditions [17,28,35,42,48,49] as it maintains physical consistencies, which are remarked next.…”
Section: B Combustion Closurementioning
confidence: 72%
“…Closures developed for the subgrid scale (SGS) reaction rate include: dynamic thickened flame model [8,9], linear eddy model [10], fractal flame-wrinkling model [11], partiallystirred reactor model [12], and Eulerian stochastic fields [13]. Another recently developed flamelet model for LES uses Scalar Dissipation Rate (SDR) closure [14,15], which is shown to be successful in RANS studies of industrial gas turbine combustors [16,17], but this approach has not been tested for LES of reacting flows in these combustors. This provides the motivation for this work.Due to large costs for experiments at realistic operating conditions of gas turbines (i.e.…”
mentioning
confidence: 99%
“…The combustion model discussed earlier in section 2 was implemented in a commercial CFD package FLUENT as described in (Chen et al, 2015;Ruan et al, 2015). This CFD package solves the necessary transport equations using finite volume methodology along with SIMPLE algorithm for pressure-velocity coupling, including the density variations in space and time.…”
Section: Cfd Setupmentioning
confidence: 99%